(untitled) (Baghdad Science Journal, 2018)
The effect of saline magnetized water irrigation on seed germination and seedling growth of wheat cultivar Iraq were studied. Irrigation water was supplemented with different levels of Sodium chloride 6, 12 or 18 mmhos/ cm in addition control treatment, and passed through a proper magnetic felid with 1000, 1250, 1500 or 2000 gaus in addition control treatment. The results showed significantly stimulated shoot development and led to the increase of germination, seedling emergence, area leaf, length of shoot and root and fresh and dry weight compared to the controls. Results also showed significant interaction between saline water and magnetized water. So, using magnetic treatment of saline water could be a promising technique for Agricultural improvement.